E-mall framework: an E-commerce community framework for small and medium industries (SMIs) / Nazri Othman - Othman, Nazri (2005)
This study proposes an e-mail framework that is going to be acting as a virtual community tools framework for the members of Small and Medium Industries (SMIs)to work together in selling their products and services to the end users. Indeed, e-mail is an aggregator to aggregate the entire products of SMIs in one place. In this study, the concept of the e-mail system is explained and the method that is used to develop its framework is described. Definitely, to come up with the framework, theoretical foundations and findings from the past literatures, journals and researches are explored, reviewed and compiled. At the end, the framework is drafted and described as a guideline to develop the exact e-mail system.